Pengaruh Good Corporate Governance Terhadap Profitabilitas Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Ervina Putri Pomalingo; Selvi; Hais Dama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study to determine the influence of the independent commisioners, board of directory, and audit committee on the profitability of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX). The data uses secondary data with a population of 113 companies listed in the consumer goods sector on the IDX. The sampling applies purposive sampling totaling 52 companies. The data analysis uses classical assumption test, hypothesis testing, and linear regression test. The results show that: 1) The independent commissioners partially does not influence the company’s profitability, 2) Partially, the board of directors does not influence the company’s profitability, 3) Partially, the audit committee influence the company’s profitability, 4) while the independent commissioners, board of directors, and audit committee simultaneously influence the company’s profitability.